Revenue administration in twenty-first century - Panda, N.K. (1994)
"Peeping into the future needs of revenue administration, the author suggests measures to strengthen administration at Tehsil, District and Division levels with abolition of Revenue Boards"
Keywords: Revenue - India; Revenue